Comments on the content of persecutory delusions: does the definition need clarification? - Freeman, D; Garety, P (2000)
Diagnostic criteria for subtypes of delusional beliefs based upon content have rarely been the subject of comment. In this article, several influential accounts of persecutory delusions are reviewed; differences and difficulties are noted, and their potential effect on cognitive psychological investigations discussed. One method of ensuring that researchers study similar phenomena is to use a more detailed definition than currently available, and therefore a new set of criteria is offered. Finally, related methodological problems in this emerging research area are highlighted. The issues discussed may stimulate further research on the content of delusional beliefs.